Exploring the digital literacy dimensions of Indonesian Generation Z teachers - Nafi, Nahar Nurun; Fauziati, Endang; Supriyadi, Slamet (Fakultas Sastra Universitas Negeri Malang, 2022)
Numerous research has revealed the digital literacy levels of generation Z students. Few academics, however, have examined the digital literacy of generation z teachers. Being a member of the digital generation and working in education, in particular, makes digital literacy necessary. The results of this study will reveal some fascinating information about how prepared Indonesian generation z teachers are to teach English online. Based on Wan Ng's theories of digital literacy dimensions, this study seeks to identify the dimensions of digital literacy among generation Z teachers (2012). This study employs a qualitative methodology. The researcher has chosen 10 generation Z English teachers who work at Salatiga schools using purposive sampling. Using Ng's views about digital literacy, the data are then divided into three groups consisting of technical, cognitive, and socioemotional dimensions. The technical dimension is the most significant component of the three categories, accounting for 92 percent of the total. Meanwhile, 73 percent and 85 percent were respectively obtained for the cognitive and socio-emotional dimensions.